Art, Imagination, and Teaching: Researching the High School Classroom - Richmond, Stuart (Canadian Journal of Education/Revue canadienne de l'éducation, 1993)
Process/product-style research into effective teaching has ignored what it means to be a good art teacher. Imagination as a quality of good teaching has similarly been ignored. I argue for the essentially imaginative nature of artistic production and appreciation, and show how this influences the art teacher’s role. As well, I develop a conceptualization of imaginative art teaching to guide the qualitative investigation of art teaching in six high school classrooms. Les recherches sur les processus et les produits relatifs à un enseignement efficace font abstraction des qualités que doit avoir un bon enseignant d’arts plastiques. On oublie également l’importance de l’imagination dans un enseignement de qualité. L’auteur soutient que la production et l’appréciation artistiques sont essentiellement de nature imaginative et explique comment cela influe sur le rôle de l’enseignant d’art plastiques. Il élabore en outre une théorie de l’enseignement des arts plastiques axé sur l’imagination, théorie servant de guide pour l’évaluation qualitative de l’enseignement des arts plastiques dans six classes au secondaire.